Análise da fadiga neuromuscular de adultas-jovens e idosas - Prusch, Samuel Klippel (2023)
The aim: To analyze neuromuscular fatigue in young and elderly women during the continuous vertical jump test. Materials and methods: The groups were composed of young and elderly women. To measure muscle electrical activity, surface electrodes in bipolar configuration were used, positioned parallel and separated by 20 mm. The electrodes were positioned longitudinally and in the direction of the muscle fibers of the muscles: vastus lateralis, biceps femoris, rectus femoris and medial gastrocnemius, according to the recommendations of SENIAM (Surface EMG for Non-Invasive Assessment of Muscles). A reference electrode was positioned on the anterior face of the tibia. An electromyograph was used to acquire the muscle EMG signal, with four input channels operating at a frequency of 2000 Hz. The raw electromyography (EMG) signals were filtered by a 5th order band-pass filter from 20 to 500 Hz. Subsequently, the values of the median frequency of the EMG signal were calculated through the first and last five seconds, of a fatigue test with a continuous vertical jumps protocol with a total duration of 30 seconds. In this test, the participants performed as many vertical jumps as possible on a CEFISE® contact mat, which in turn was connected to a computer that calculated the flight time, the height obtained and the power exerted on the mat. The applied technique was the Counter Movement Jump, without the help of the upper limbs. EMG and mat data were synchronized. Data were submitted to descriptive statistics. Normality in data distribution was verified using the Shapiro-Wilk test, homogeneity using the Levene test. For comparisons in the characterization of the groups and in the variables related to the jumps, between the different groups, the t test for independent samples was used. For comparisons within the same group, the paired t test was used. The significance level for all tests was 5%. The results showed that the group of young women obtained higher averages in the development of jumps (height and gross and normalized power) than elderly women. However, the elderly women, despite this lower performance, showed an equal neuromuscular activation (vastus lateralis, rectus femoris and medial gastrocnemius) or greater (biceps femoris) than the group of young people, in order to present the fatigue of the biceps femoris muscle. Finally, regarding the comparison of neuromuscular activation within the same group (five first X last five), the young women showed differences in the rectus femoris and medial gastrocnemius muscles, with higher values for the initial jumps. For the group of elderly women, the muscles that showed differences (higher values in the initial jumps) were the vastus lateralis, rectus femoris and medial gastrocnemius. In view of this, the use of EMG appears as a method that can contribute to a better understanding of the muscular system, as in neuromuscular fatigue protocols.